Sanitasi dan Kualitas Air Minum pada Depot Air Minum (DAM) - Sumiyati Sumiyati; Agus Subagiyo; Arum Lusiana (Jurnal Riset Kesehatan, 2015)
This is a descriptive research about the sanitation and the quality management of drinking water stands in Banyumas. The data were collected through interviews, observations and laboratory tests. The results show that drinking water stands sanitary conditions in Banyumas in 2014 with excellent category as much as 57.15%, 21.4% is in good category, 14.3% is in quite category and 7.15% is in unfavorable category, the physical quality of drinking water meets health standards: colorless, odorless and tasteless, chemical quality of drinking water qualify chemically with normal pH, 78.6% drinking water stands are not contaminated with coli form bacteria and 21.4% contaminated with coli form bacteria. The sanitary conditions categories are excellent, good, quite, and unfavorable. While the physical and chemical quality meets health standards, but there are still stands that contaminated with coli form bacteria. We suggest the owner of drinking water stands to increase sanitation hygiene and examine the water refill samples every month. It is also important for the employees to improve healthy behavior and cleanliness. DKK Banyumas needs to improve guidance and supervision for the owner of drinking water stands to manage the sanitation and hygiene well so that the quality of the product is assured.